Behavior of adhesively bonded engineered wood – Wood chip concrete composite decks: Experimental and analytical studies. (30th June 2020) - Fu, Qiuni; Yan, Libo; Ning, Ting; Wang, Bo; Kasal, Bohumil
Highlights: Behaviour of adhesively bonded timber-wood chip concrete decks was investigated. Epoxy and polyurethane can provide rigid connection for timber-concrete composites. Wood chip concrete with engineered wood shows potential as structural slab. A simplified method is proposed to predict bending stiffness of the composite decks. Abstract: In this study, epoxy and polyurethane (PUR) were used to glue five medium-sized (i.e. length of 2300 mm and width of 215 mm) engineered timber-concrete composite decks to investigate their composite action and flexural behavior under four-point bending tests. Cross laminated timber (CLT), laminated veneer lumber (LVL), plain concrete (PC) and an innovative type of wood chip concrete (WCC) were used. The five specimens were WCC-Epoxy-LVL, WCC-PUR-LVL, WCC-Epoxy-CLT, WCC-PUR-CLT and PC-Epoxy-LVL. All the specimens showed linear load-deformation responses approaching the final failure. Ultimately, all the decks failed by either compressive crushing of concrete or wood parts, rather than the debonding at the wood-concrete interface, indicating a good composite action of the timber-concrete composite decks. Compared with the specimens made of PC, the flexural stiffness and load-carrying capacity of the specimens made of WCC reduced by around 20%. Nevertheless, the thermal conductivity of WCC could be reduced by 30%, interpolated from the chart in an independent study. Lastly, the authors analytically predicted the effective bending stiffness and mid-span deflection for each specimen, considering the shear flexibility of transvers layers (stressed perpendicular to fiber direction) in engineered wood as partial composite action and assuming a perfectly rigid bond at wood-concrete interface.